THE STRATEGY OF CONSTRUCTING OF UNIVERSITY IDENTITY SYSTEM IN PUBLIC UNIVERSITIES IN SHENYANG CITY, CHINA - Yi, Wang; Howattanakul, Sutida; Pruettikul, Sataporn (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) To study the factors that affect the identity images of Shenyang Universities. (2) To study the identity image strategies of Shenyang Universities This research was a mixed method research, including quantitative research and qualitative research. This paper implemented a quantitative study on the components of the identity system construction of 19 public universities in Shenyang. The researchers were randomly selected from 19 public universities in Shenyang. The main respondents were managers and teachers with work experience in 19 public universities in Shenyang, as well as junior college students, undergraduate students, master’s degree and doctoral students studying in 19 universities, a total of 700 samples. The tools used for data collection were semi-structured interview tables and questionnaire stars. Exploratory factor analysis (EFA) was used to reduce irrelevant variables. Using the purposive sampling method, 15 key information providers from three public universities in Shenyang (Northeast University, Liaoning University, Lu Xun Academy of Fine Arts), The tool used for data collection was a semi-structured interview form. The statistical data used for data analysis were frequency, percentage, mean value and standard deviation, and exploratory factor analysis and content analysis are used. The research findings revealed that; (1)The components that affected the identity of Shenyang Public Universities: UVIS, UBIS and UMIS; and (2) The managerial guidelines on Shenyang Public University Identity System Development Strategy: The evaluation system of University visual identity system included four items: external image, internal image, personality image and artistic image.The evaluation system of university concept identification system included four items: educational philosophy, educational concept, cultural perception and school running characteristics.The evaluation system of behavior recognition system in Colleges and universities included seven items: teacher quality and organizational system, cultural activities, teaching philosophy, scientific research development, study style service system, and example system.